REALISASI TINDAK TUTUR BERDASARKAN PRINSIP KONVERSASI PADA TRANSAKSI JUAL-BELI DI PASAR 10 ULU PALEMBANG (KAJIAN PRAGMATIK) - Belinda, Mentari Tira; Wardiah, Dessy; Heru, Agus (Universitas Negeri Surabaya, 2019)
This study aims to describe how the realization of speech acts is based on the principle of conversion in buying and selling transactions at the Palembang Ulu 10 Market. The type of research is qualitative descriptive research. The data sources of this study are traders and buyers at the Palembang Ulu 10 Market. This research data is in the form of speeches from traders and buyers when conducting transactions that contain elements of the principle of conversion. Data collection techniques in this study used the record method, see, note, observation. The data analysis technique used is content analysis. The researcher concluded that the realization of speech acts based on the principle of conversion included the principle of politeness and the principle of cooperation. The results of the research show that the dominant politeness principle used in transactions at the Market Ulu 10 Palembang is the maxim of wisdom, while the principle of cooperation, which is often used by traders and buyers, is the maxim of quantity.